Critical sustainability events and perceived roles of academic leaders at a leading university in sustainability: CIT case study - Anete Veidemane; Daniela Craciun; Barend van der Meulen (Discover Sustainability)
Abstract This case study explores the perceived roles of academic leaders in critical sustainability events at a leading university in sustainability—the University of Auckland (UoA). The UoA was selected because of its high position in the Times Higher Education (THE) Impact Ranking (1st in 2019 and 2020) based on its contribution to Sustainable Development Goals (SDGs). Employing the critical incident technique (CIT) and semi-structured interviews, university staff were asked to reflect on the meaning of a sustainable university, critical sustainability events, and the roles of academic leaders in these events. The interviews revealed that, while a multidimensional and holistic vision of a sustainable university is beneficial for engaging diverse stakeholders, three transformation tensions emerge as the discussion moves from vision to implementation: priorities (competing sustainability dimensions), pace (desired speed of transformation), and process (desired consultation for transformation). This study identified five perceived roles of academic leaders: no role, support, drive, divert, and block. These roles were positioned along two axes: leadership stance (favourable to unfavourable) and leadership behaviour (passive to active). The leadership stance was influenced by competing priorities as well as resource and authority constraints. More active leadership behaviour signalled a stronger leadership stance and role (e.g., drive, block). No single role was found to be optimal for every situation. Rather, each role can be utilised to address transformation tensions (priorities, pace, and process) in various ways. In total, 16 critical sustainability events (CEs) were identified by staff; most (81%) took place within the last 5 years (2019–2023). CEs were classified as external (not initiated by the university) or internal (initiated by the university). The two most frequently recalled CEs were external–COVID-19 and THE Impact Ranking– which affected the university’s sustainability journey across multiple dimensions. However, the majority of identified CEs were internal CEs (75%) and included several central-level strategies and policies (e.g. sustainability strategy and flight policy). These insights also revealed that the CEs should not be viewed in isolation since more recalled CEs, highly visible and centralised, were often underpinned by less prominent CEs (e.g. data monitoring). Notably, the recent change in central-level leadership, although less frequently recalled as a CE (10%), was mentioned by the majority of interviewees (> 60%).